2020
DOI: 10.1097/ana.0000000000000731
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Airway Management During Awake Craniotomy: Comparison of 5 Techniques in a Cadaveric Model

Abstract: Background: During awake craniotomy, securing the patient's airway might be necessary electively or emergently. The objective of this study was to compare the feasibility of airway management using a laryngeal mask airway (LMA) and 4 alternative airway management techniques in an awake craniotomy simulation.Methods: After completing a questionnaire, 9 anesthesia providers attempted airway management in a cadaver positioned to simulate awake craniotomy conditions. Following the simulation, participants rated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Supraglottic airway devices used during awake surgeries are a feasible option. According to some authors, these should be the first choice for emergency airway management, followed by fiberoptic intubation through the laryngeal mask airway ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supraglottic airway devices used during awake surgeries are a feasible option. According to some authors, these should be the first choice for emergency airway management, followed by fiberoptic intubation through the laryngeal mask airway ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that a laryngeal mask airway (LMA) was adequate and timely for securing the airway compared with intubation with a direct or video laryngoscope. In a subsequent study utilizing a cadaveric model, Gruenbaum et al 17 confirmed that the LMA was the quickest and most reliable primary technique for securing an emergency airway during an awake craniotomy.…”
Section: Scenarios In Neuroanesthesia Simulationmentioning
confidence: 95%
“…These models can simulate complex cranial base surgery, intraventricular tumor resection, and anterior cervical discectomy and fusion 10 . Anesthesiologists can practice managing significant blood loss and resuscitation, traumatic injuries, and airway complications 10,17,18 …”
Section: Current Simulation Modelsmentioning
confidence: 99%
See 2 more Smart Citations